Extending a Lifeline or Cutting Losses? : The Effects of Conflict on Household Receipts of Remittances in Pakistan - Ghorpade, Yashodhan (Elsevier, 2018)
The author examines the causal effects of long-term exposure to conflict, measured at the micro level, on households’ receipt of remittances, among households residing in areas affected by the 2010 floods in Pakistan. Using a dataset of 7802 households, representative of all flood-affected areas of Pakistan in 2010, IV estimation is employed to overcome the endogeneity of conflict exposure and remittance receipts, and control for a range of confounding factors. Contrary to the literature from country-level case studies, it is found that long-term exposure to conflict reduces households’ likelihood of receiving any remittances at all, as well as the average amounts of remittances received. However for households in the lowest food consumption expenditure quintile, conflict has a positive effect on the likelihood of remittance receipts, which provides evidence for the existence of heterogeneous effects as well as a significant micro–macro gap in understanding the causal effects of conflict on remittance receipts.